Characteristics of Geology, Geochemistry, Geophysics in Assessing the Geothermal Potential of the Bonjol Region, Pasaman, West - Eddy Mulyadi; Arif Munandar (GoAcademica Research & Publishing, 2023)
The purpose of this study was to determine the Characteristics of Geology, Geochemistry, Geophysics in Assessing the Geothermal Potential of the Bonjol Region, Pasaman, West Sumatra. The Bonjol geothermal area is included in the Bonjol District, Pasaman Regency, West Sumatra Province. The rocks in the study area can be divided into 13 rock units, namely two sedimentary rock units, 10 volcanic rock units, and one surface sediment unit, while geothermal manifestations in the research area are scattered in the central part which is dominated by the emergence of hot springs in Padang Baru, Takis River, Limau River, and Langkuik/Kambahan River. In addition to hot springs, alteration rocks are also found around Ds. Blimbing and in the northwestern part of the research area are both past alterations.